My once and future duke ebook The wagers of sin. - Linden, Caroline (The Wagers of Sin, 2018)
What happens at the infamous Vega Club . . . Sophie Campbell is determined to be mistress of her own fate. Surviving on her skill at cards, she never risks what she can't afford to lose. Yet when the Duke of Ware proposes a scandalous wager that's too extravagant to refuse, she can't resist. If she wins, she'll get five thousand pounds, enough to secure her independence forever. Stays at the Vega Club . . . Jack Lindeville, Duke of Ware, tells himself he's at the Vega Club merely to save his reckless brother from losing everything, but he knows it's a lie. He can't keep his eyes off Sophie, and to get her he breaks his ironclad rule against gambling. If he wins, he wants her—for a week. Until now. A week with Jack could ruin what's left of Sophie's reputation. It might even cost her her heart. But when it comes to love, all bets are off . . .